Needs Analysis for the Development of Flipchart-Based Learning Media with the Jigsaw Method to Improve Students' Concept Understanding of Vector Material in Class X SMA Bengkulu City - Annisa Bella Haryanti (Indonesian Journal of Pedagogy and Teacher Education, 2023)
The purpose of this study was to analyze the need for developing learning media in the form of flipchart media with the jigsaw method to improve students' understanding of concepts in class X vector material. The method used is quantitative descriptive method with data collection techniques through observation and interviews accompanied by documentation and literature review to review related research. From the results of the analysis carried out in physics learning, many learning media use print media. This is because the use of non-print media that has been used previously has several shortcomings when applied in offline learning but does not rule out the possibility of continuing to use it in offline learning. From the results of the data obtained, printed media in offline learning makes students better understand the material presented. This shows that there is a need for the development of more interesting learning media, for example illustrated learning media with flexible access that can be used in offline and online learning. Based on the results of the research that has been done, it shows that there is a need for appropriate media development in physics learning. One of the developments that can be done is to develop flipchart learning media using the jigsaw method.